The experiences of male adolescents who have been in a toxic relationship - Putu Divariani; Putu Nugrahaeni Widiasavitri (Jurnal Psikologi Ulayat: Indonesian Journal of Indigenous Psychology)
This study explores the experiences of male adolescents in toxic relationships and their considerations for leaving such relationships. Contrary to common perceptions, females can also exhibit toxic behaviors, significantly affecting male victims. Using a qualitative phenomenological approach, researchers analyzed data from five male adolescents in Bali who experienced toxic relationships during high school. The data were processed using Interpretative Phenomenological Analysis (IPA), revealing five main themes: 1) the journey of the relationship; 2) the role of family; 3) forms of toxic partner behavior; 4) factors influencing decisions to stay or leave; and 5) psychological responses. These findings highlight the complex dynamics of toxic relationships involving male adolescents.